EXPORT OF UKRAINIAN GRAIN: LOGISTICAL ASPECT - Гирич, Сергій; Василишина, Ольга (SWorldJournal, 2025)
The paper examines the logistical challenges of exporting Ukrainian grain to global markets. It highlights that the Russian invasion of Ukraine led to the disruption of supply chains for Ukrainian grain exports, which in turn caused a decline in grain exp